2013
DOI: 10.1158/0008-5472.can-12-4479
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mast Cell–Stromal Cell Interactions Promote Growth of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) exists in a complex desmoplastic microenvironment, which includes cancer-associated fibroblasts (also known as pancreatic stellate cells, PSCs) and immune cells that provide a fibrotic niche that impedes successful cancer therapy. We have found that mast cells are essential for PDAC tumorigenesis. Whether mast cells contribute to the growth of PDAC and/or PSCs is unknown. Here we tested the hypothesis that mast cells contribute to the growth of PSCs and tumor cells, thus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 52 publications
4
149
0
3
Order By: Relevance
“…Previous studies have demonstrated that angiogenesis and Ki-67-positive fraction are essential for the development and progression of tumours (27)(28)(29)(30)(31). In addition, numerous studies have suggested that increased tissue MVD and Ki-67 proliferation index, which were individually assessed, were correlated with a poor prognosis in PDACP (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that angiogenesis and Ki-67-positive fraction are essential for the development and progression of tumours (27)(28)(29)(30)(31). In addition, numerous studies have suggested that increased tissue MVD and Ki-67 proliferation index, which were individually assessed, were correlated with a poor prognosis in PDACP (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expanded our analysis generating additional Gdf- 15- (15,16) that also stably expressed a luciferase reporter gene that was used for bioluminescence imaging (17) (Figure 3A). KPC control or KPC Gdf-15-knockdown clones were then orthotopically injected into the tail of the pancreas of C57BL/6 albino mice, and tumor development was visualized.…”
Section: Ras Mefsmentioning
confidence: 99%
“…Analysis of a pancreatic cancer model mouse revealed the contribution of mast cells during pancreatic carcinogenesis, and detailed mechanisms of their activation were examined thereafter. Co-culture of mast cells with PSCs led to mast cell activation, characterized by tryptase and tumor necrosis factor-a release in the culture supernatant [91]. In turn, mast cell-derived IL-13 and tryptase promoted the proliferation of PSCs, leading to further fibrogenesis.…”
Section: Modulation Of the Immune System In Pancreatic Cancermentioning
confidence: 99%